(untitled) (Revista de História Regional, 2009)
The idea of the delay or archaism of the elites from Campos Gerais do Paraná supported in the great country properties and extensive creation appears spread in academic works, literature and the media, influencing the proper course of the politics of regional development. However, we defend the thesis of that the modernity these local elites in the long of history because of constant modernizations of the regional productive process and the production of the social exclusion.